Food supplements consumption and the role of pharmacies: a north-eastern Italy observational study. (20th October 2021) - Mazzilis, G; D'Angelo, M; Brunelli, L; Colautti, L; Cojutti, P; Arnoldo, L; Parpinel, M
Abstract: Background: Even if the food supplement industry is one of the fastest growing worldwide, the inappropriate use of these products can potentially cause harms. Considering the key role played by pharmacists in advising citizens on the purchase of food supplements, this cross-sectional observational study evaluates pharmacists' knowledge, attitudes and practice on this topic. Methods: From September 2020 to February 2021, an online questionnaire implemented through the EU-Survey tool, was administered to pharmacists of both public and private authorized pharmacies of the Friuli-Venezia Giulia (FVG) Region (Italy). The 47 multiple-choice questions about pharmacists' knowledge (20), attitudes and practice (27), were followed by a sociodemographic section (7 items) collecting data about sex, age, years of experience, degree, role within pharmacy (owner, employee). Descriptive analyses, Chi-square, Shapiro-Wilk and Mann Whitney tests were used and a p-value<0.05 was considered as statistically significant. Results: A sample of 232 questionnaires was collected, 70.7% of which from women. Most responders (77.2%) had a Pharmacy degree, with owners representing the 34.5%. The 61.2% of pharmacists had at least 10 years of experience. Knowledge was generally poor with just 49.2% of the sample scoring above the median value of 11 but higher among pharmacists with more than 11 years of experience. Lesser-known aspects were the possible link between cancer and multivitamin's abuse and presence of non-labeled agents in food supplements. Responders < =10 years of experience felt more unprepared about vitamin's dosage and in counselling particular groups of patients (p < 0.05). Employees more frequently reported the attitude to purchase food supplements under patient specifical request (p < 0.05). Conclusions: Pharmacists' knowledge about food supplements is scarce and young professionals in particular need further education to ensure a safe and effective purchase of these products to patients. Key messages: The use of vitamin supplements is growing but their consumption needs to be evaluated by expert and qualified professionals. Pharmacists play a key role in counselling people about food supplements but need continuous professional education to give adequate advice.